THE IMPACT OF ARABIC LANGUAGE ON PRODUCING FRAGMENTS - Bushra Abu- Faraj; Sukyna Ali (European Scientific Journal, ESJ, 2015)
The present study aims at examining the relationship between first language (Arabic) proficiency and second language (English) writing performance of 35 students from the University of Jordan. In addition, we are also interested in testing the impact of using L1 (Arabic) on producing sentence fragments. For that purpose, we have set two surveys to examine the most common type of fragments produced by our study population. The first survey was a multiple choice survey consisting of 8 sentences written in Arabic along with 3 different choices. The second survey was a sentencetranslating one consisting of 6 Arabic sentences and the participants were asked to translate them on their own. Our study population was third-year English language and literature students. The results revealed by our study show that missing-subject fragments were the most common type of fragments produced. The results obtained by our study support the results obtained by previous studies which state that the most common type of writing errors produced may include sentence fragments and other writing errors such as subject-verb agreement and articles. These writing errors are mainly produced due to the negative impact of L1 transfer as L1 speakers rely on their mother tongue when translating certain sentences into the target language L2.The study concludes with some recommendations for teachers to attract the students’ attention to such errors.